Juridical Analysis of Value Added Tax Dispute on the Sale of Foreclosed Collateral (AYDA) with Written-Off Receivables as Recovery Income - Ahmad Munir; Sri Hartini; Annisa Aminda (JURNAL MAHASISWA YUSTISI, 2026)
This study aims to examine the juridical aspects of Value Added Tax (VAT) disputes arising from the sale of foreclosed collateral (Agunan yang Diambil Alih/AYDA) by financing institutions after the debtor’s receivables have been written off and the sale proceeds recorded as recovery income. The legal issue focuses on whether such a transaction constitutes a taxable supply under VAT law and how recovery income should be treated under accounting and tax regulations. The research employs a normative juridical method, combining statutory and conceptual approaches, and utilizes secondary data derived from tax legislation, accounting standards, and tax court decisions. The study reveals that the Directorate General of Taxes (DGT) interprets AYDA sales as taxable transactions, while taxpayers argue that these transactions merely recover losses rather than generate new economic value. From an accounting perspective, recovery income is treated as non-operational income, while under tax law, it is already subject to income tax (PPh). The findings conclude that the sale of AYDA should not be subject to VAT, as it does not constitute a new supply of goods; however, since the issuance of Government Regulation No. 44 of 2022 and Minister of Finance Regulation No. 41/PMK.03/2023, AYDA sales have been explicitly classified as taxable transactions